2017
DOI: 10.15389/agrobiology.2017.4.785eng
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION of NK-lysin, blvr, ifn-a AND BLOOD CELL POPULATIONS IN COWS INFECTED BY BOVINE LEUKEMIA VIRUS

Abstract: At now, it is impossible to prevent or control the spread of retroviral infections, in particular, bovine leukemia virus (BLV). The existing methods of vaccination and detection of infected animals remain insufficient (G. Gutiérrez et al., 2014; M. Nishiike et al., 2016) which necessitates further investigations of the interactions between pathogen and host organism. Previously, we obtained evidence that a common characteristic for BLV infected animals with moderate and high leukocytosis was the increase in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Interestingly, there were also correlations between blvr, pol, dc1, and ago2 gene expressions ( Table 6). In our previous studies, blvr gene expression was also increased in BLV infected animals; however, its expression didn't correlate with other features (16). Generally, blvr is highly expressed in juvenile lymphocytes and its expression gradually decreases during terminal differentiation (19).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, there were also correlations between blvr, pol, dc1, and ago2 gene expressions ( Table 6). In our previous studies, blvr gene expression was also increased in BLV infected animals; however, its expression didn't correlate with other features (16). Generally, blvr is highly expressed in juvenile lymphocytes and its expression gradually decreases during terminal differentiation (19).…”
Section: Resultsmentioning
confidence: 80%
“…In our previous studies, we demonstrated that cows, which are infected with BLV virus, have lower NK-lysin gene expression (that is the functional marker of T and NK killers) and have an increased thrombocyte count as compared to uninfected cows (16). It could indicate that the major BLV-induced infection event is the suppression of the host immune system.…”
Section: Introductionmentioning
confidence: 98%
“…К о м п л е к с н о с т ь в з а и м о д е й с т в и я о б о л о ч е ч н ы х б е л к о в в и р у с а с б е л к а м и п л а з м а т и ч е с к о й м е м б р а н ы к л е т о к х о з я и н а. Ранее мы рассматривали основы и последствия связывания оболочечного белка BLV, кодируемого геном env, с клеточным рецептором адаптерного комплекса (adaptor-related protein complex-3 -AP-3), участвующего в транспорте белков в лизосомы (3). Нами было обнаружено, что у инфицированных BLV коров экспрессия гена, кодирующего рецептор AP3D1, выше, но она не коррелирует с увеличением количества лимфоцитов, что обычно рассматривается как предлейкозное состояние (4). Другой мишенью рецепции продуктов гена env BLV, способствующей слиянию инфицированных и свободных от инфекции клеток, служит трансмембранный транспортер катионных аминокислот SLC7A1/CAT1 (5,6).…”
unclassified
“…Известно, что Tax индуцирует увеличение экспрессии многих генов хозяина, в частности фактора некроза опухолей альфа -TNFα (67,68). В наших собственных исследованиях было обнаружено, что одним из наиболее общих изменений у инфицированных BLV коров (независимо от происхождения и хозяйств, в которых они содержались), кроме различий в количестве тромбоцитов (69), оказалось уменьшение экспрессии NK-лизина -одного из основных белков цитотоксических гранул Т-киллеров и NK-клеток, что отражает угнетение факторов врожденного иммунитета (4).…”
unclassified